A method for the permeabilization of live Drosophila melanogaster larvae to small molecules and cryoprotectants. Issue 1 (1st October 2020) - Murray, Alex; Palmer, Daniel; Bennett, Daimark; Dwarampudi, Venkata; Pedro de Magalhães, João
ABSTRACT: The larvae of Drosophila melanogaster is a model organism widely used to study the muscular and nervous systems. Drosophila larvae are surrounded by a waxy cuticle that prevents permeation by most substances. Here we develop a method to remove this layer, rendering the larvae permeable to small molecules without causing death, allowing the larvae to develop to adulthood and reproduce. Permeability was assessed using fluorescein diacetate dye uptake, and mortality upon exposure to toxic levels of ethylene glycol (EG) and Dimethyl sulfoxide (DMSO). Potential uses for this method include drug delivery, toxicity assays, cryopreservation, staining, and fixation.